In vitro characterization of probiotic properties of a novel strain Lactobacillus crustorum F11 isolated from human milk - Handa, Shweta (Indian Journal of Dairy Science, 2016)
In the present study, isolation of potential probiotic lactic acid bacteria was done from the human milk. In total 15 LAB were isolated and identified on the basis of physiological and biochemical characterization. Preliminary screening was done on the basis of antagonistic potential and isolate F11 has shown strongest inhibition of most of the food borne and pathogenic microorganisms. The genomic level identification had been performed and bacteria F11was identified as Lactobacillus crustorum. Further, its probiotic potential was assessed and was found to tolerate low pH, high bile salt concentration, highly hydrophobic, strong autoaggregability and was sensitive for tested antibiotics. The strain possessed the cumulative probiotic score of 95.8%.Â This is first time reported in literature to evaluate probiotic features of human milk in detail. Thus study showed that the addition of breast milk probiotic isolate L. crustorum F11 to infant feed formulas could be a new alternative to mimic some of the functional effects of human milk in children who are not breastfed.